PREDICTIVE VALUE OF TIMI SCORE IN PATIENTS WITH NON-ST ELEVATION MYOCARDIAL INFARCTION - ALI, Q; ALI, L; KHATTAK, MSK; SHAHID, NA (Biological and Clinical Sciences Research Journal, 2023)
This retrospective study was conducted in the Department of Cardiology in tertiary care hospitals during June 2022 and June 2023 to evaluate the power of TIMI risk score in predicting 14-day mortality in patients with NSTEMI presenting in the cardiac center of a local hospital for determining prognostic value to the score in our cohort. The study included 250 patients aged > 18 years presenting with NSTEMI. A proforma was used to collect data, including demographic data, baseline investigations, detailed history, TIMI score at the time of presentation, and patient status after 14 days of hospital stay. All patients followed ACS protocol, and NSTEMI was managed according to current guidelines. Results showed that the predictive value of the TIMI score, AUC, was 0.788 (95% CI: .688-.886), its sensitivity was 77.80%, and its specificity was 68.08%. In subjects with a TIMI score ≥4 (11.2%, n=12/105), the 14-day mortality rate was more significant than those with a TIMI score <4 (3.4%, n=5/145) (P<0.001). Multivariate analysis reveal that TIMI risk and cardiac arrest were independent predictors of 14-day mortality. TIMI risk score is a simple and useful tool for risk stratification in NSTEMI patients. Its use will enable clinicians to adopt precise and strategic interventions for these patients.